Collating, processing and analysing pig carcase quality and condemnation data to monitor and control health and welfare in the Scottish pig industry - Gomes, Mafalda Viegas Dias (2023)
Dissertação de Mestrado Integrado em Medicina Veterinária, área científica de Sanidade Animal